Record Keeping Systems and Service Delivery in Uganda: Case of Kabale District Local Government - Bosco, Turyasingura John; Moses, Agaba; David, Kabagambe Jesse; Godfrey , Barigye (Asosiasi Dosen Peneliti Ilmu Ekonomi dan Bisnis Indonesia, 2023)
The purpose of this study was to determine how the Kabale District Local Government's service delivery was impacted by its record-keeping procedures. The study's end variable was the provision of services, and its predictor factors were the efficiency with which the records management systems function. Prior to the investigation, a cross-sectional survey was conducted. It was decided to use the information from 86 respondents for both a quantitative and a qualitative study. Since descriptive analysis required that a single variable and its attributes be given together with the data, frequency tables were used to interpret the data. The bivariate correlations between the predictor elements and the dependent variable were examined using a Pearson correlation matrix. A linear regression model was used to fit the data. Record keeping systems (R=889) has a favorable influence on the capacity of the local administration of the Kabale District, per the research findings from the regression model. The main conclusion of this study is that the auditing process has an impact on service delivery at the Kabale District Local Government, as evidenced by the findings and discussion. This is in line with the researcher's later discoveries. The respondents' replies to the question of whether Integrate is observed in accordance with the auditing process showed that 90.7% of them agreed with the claim and 9.3% were unclear. When offering services, the study advises emphasizing the auditing process. To do this, emphasis should be placed on relationship-building, objectivity, punctuality, and communication.